2022
DOI: 10.1111/1751-2980.13120
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of signet‐ring cell carcinoma derived from gastric fovelar epithelium

Abstract: We aimed to investigate the immunophenotype, differential diagnosis, and clinicopathological characteristics of signet-ring cell carcinoma (SRCC) derived from gastric foveolar epithelium.Methods: Clinical characteristics, endoscopic findings, histopathological features, and follow-up data of seven cases of SRCC derived from gastric foveolar epithelium with small intramucosal lesions were analyzed.Results: Seven patients with a mean age of 38.3 years were diagnosed with SRCC derived from gastric foveolar epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Atrophy can occur in the intestinal type of gastric cancer as well as in the gastric type. The previous study conducted by the authors of the present study reported that Helicobacter pylori infection leads to gastric small concave epithelial type signet-ring cell carcinoma [ 18 ]. In severe atrophy of the lamina propria glands, there is no cellular heterotypic hyperplasia or intestinal metaplasia, including complete intestinal metaplasia and incomplete intestinal metaplasia.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Atrophy can occur in the intestinal type of gastric cancer as well as in the gastric type. The previous study conducted by the authors of the present study reported that Helicobacter pylori infection leads to gastric small concave epithelial type signet-ring cell carcinoma [ 18 ]. In severe atrophy of the lamina propria glands, there is no cellular heterotypic hyperplasia or intestinal metaplasia, including complete intestinal metaplasia and incomplete intestinal metaplasia.…”
Section: Introductionmentioning
confidence: 73%
“…Four types of gastric mucosal atrophic lesions were proposed according to their pathological stages and characteristics as follows: (1) stage I gastric mucosa gland atrophy: mild atrophy and a smaller volume of the gastric mucosa glands; (2) stage II compensatory proliferative atrophy: polar compensatory hyperplasia and reduced gastric mucosa glands; (3) stage III intestinal metaplastic atrophy (intestinal metaplasia is a transformation of the cells in the lining of the upper digestive tract, often the stomach): a dominant intestinal metaplasia type and the intestinal metaplasia cells accounted for > 30% of the entire gland; and (4) stage IV smooth muscle proliferative atrophy: proliferative atrophy of smooth muscle fragments and smooth muscle fibres of different sizes and shapes appeared in the lamina propria. These four types of classifications are based on a previous study [ 18 ]. Mastering the histological characteristics and pathological stages of atrophic conditions is beneficial to clinicians for the precise treatment of atrophic lesions of the gastric mucosa and the tracking of malignant cell transformation, which is important for reducing the occurrence and development of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This study focused on the GSRCC nomogram because of its controversial prognosis. Compared to other types of GC, GSRCC has unique tumorigenic properties and atypical epidemiological distribution ( 9 ). Zu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite constantly changing terminology, the lack of strict diagnostic criteria, and unestablished investigative protocols, which all together pose additional issues calculating the incidence of the disease, it is clear that a true prostatic SRCC is extremely rare, with an estimated prevalence of 0.02% among all prostate adenocarcinoma cases [ 5 ]. Due to its rare nature, the close epidemiological relation to the gastrointestinal tract, and diffuse, lateral, submucosal growth pattern, a diligent diagnostic workup for differentials must be carried out since the location of the primary tumor may be an independent factor for the cause-related survival and virulence of the disease [ 7 , 13 ]. The investigations should include upper gastric endoscopy, colonoscopy, cystoscopy, and abdominal computed tomography to exclude metastatic involvement of the prostate [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variant is predominantly observed in the gastrointestinal tract, emphasizing the stomach and colon; therefore, these organs are the first ones to be ruled out in suspicion of metastatic disease and are a reference point in other-organ signet-ring cell carcinoma (SRCC) cases [ 5 ]. However, it is not an uncomplicated process since early gastric SRCC is nearly macroscopically invisible, meaning that in most cases, it is diagnosed rather late, posing a great diagnostic and therapeutic challenge [ 7 ].…”
Section: Introductionmentioning
confidence: 99%